A Systematic Literature Review of Religiosity On Customer Decisions in Choosing Syariah Bank - Siti Erdini Yulanzy (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to identify the influence of religiosity on customer decisions in choosing Islamic banks using the Systematic Literature Review (SLR) approach. The SLR process includes the stages of identification, assessment, and interpretation of literature, which resulted in 18 articles from 18 journals published between 2015 and 2022, indexed by SINTA, and have E-ISSN. The results of the study indicate that the influence of customer religiosity still has opportunities and challenges to be improved. This can be seen from the low level of customer religiosity, which is indicated by the lack of religious calling that influences their attitudes and behavior, as well as limited understanding of the prohibition of usury and the use of Islamic banks only for profit. Indicators of religiosity that play a role in influencing customer decisions to choose Islamic banks include the quality of Islamic products, avoidance of usurious transactions, profit sharing principles, and Islamic features. There is a gap in results between the samples studied, which can be a research gap for further studies. Recommendations for improving customer decisions include increasing religiosity, fulfilling customer needs, and the effectiveness of Islamic financial literacy. This study can be used as a reference for further research on the role of religiosity in influencing customer decisions in choosing Islamic banks.